Praktik Akuntansi Pada Usaha Mikro, Kecil, Dan Menengah (Umkm) Di Desa Situmeang Habinsaran, Tapanuli Utara - Tetti Manullang (Journal on Education, 2024)
This study aims to analyze the accounting practices of Micro, Small, and Medium Enterprises (MSMEs) in Situmeang Habinsaran Village and to identify the challenges that hinder the implementation of accounting practices, particularly in the preparation of financial statements. This research uses a qualitative approach with a case study method. Data for this study was collected through three primary techniques: in-depth interviews, observation, and documentation. The data obtained was analyzed using thematic analysis. The findings indicate that most MSMEs in this village only perform basic financial record-keeping manually, without adhering to standard accounting practices. These records are limited to daily transactions and do not accurately reflect the financial position of the business, leading to difficulties in making sound financial decisions. Additionally, the lack of accounting knowledge among MSME operators, due to insufficient education or accounting training, hinders them from preparing formal financial statements such as balance sheets, income statements, and cash flow statements. Inconsistent transaction documentation also poses a serious problem, negatively impacting the accuracy of financial statements and MSMEs' access to external financing. The study emphasizes the need for intensive accounting training and the adoption of accounting technology to enhance MSMEs' capacity to prepare more structured and standard-compliant financial statements, which in turn will strengthen their competitiveness and economic resilience in an increasingly competitive market. Support from the government and related institutions is also needed to encourage better accounting practices and the use of accounting technology among MSMEs..